(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Violence against children is widespread and affects millions of children globally. Violence against children occurs in various forms including physical violence, maltreatment, bullying, emotional or psychological violence, forced and bonded labour, and trafficking. To prevent child abuse, it is essential that a high degree of awareness is essential amongst all stakeholders including parents, educators and medical professionals. The common thread among all studies conducted in medical professionals is the lack of focused training and sensitisation that can enhance the ability to detect such cases and respond to them promptly Objective: To Assess Awareness Regarding Child Abuse and Neglect among Emergency Medical Professionals in Pune Methodology: As part of an awareness initiative by the Institute, an online session was conducted for the Emergency Medical Professionals (EMP) in Pune city. 65 Emergency Medical Professionals working in various hospitals located around all parts of Pune participated in the session. After the session was completed, informed consent was taken from the participants for answering a questionnaire based on the subject. The questionnaire chosen for the study was Child Abuse and Neglect Awareness Scale (CANA-S) a pretested and validated tool. The CANA-S tool comprises 4 sections, each section comprising a subscale dedicated to one of the major categories of child abuse and neglect i.e. physical abuse, sexual abuse, emotional abuse, and neglect. Conclusion: Though the overall awareness about Child Abuse and Neglect is satisfactory, further training programs should be encouraged, to achieve near 100 % awareness amongst EMS professionals in order to prevent and report every single case of Child Abuse and Neglect.